Rhizobia population was favoured during in situ phytoremediation of vanadium-titanium magnetite mine tailings dam using Pongamia pinnata. (December 2019) - Yu, Xiumei; Kang, Xia; Li, Yanmei; Cui, Yongliang; Tu, Weiguo; Shen, Tian; Yan, Min; Gu, Yunfu; Zou, Likou; Ma, Menggen; Xiang, Quanju; Zhao, Ke; et al.
Abstract: Mine tailings contain toxic metals and can lead to serious pollution of soil environment. Phytoremediation using legumes has been regarded as an eco-friendly way for the rehabilitation of tailings-laden lands but little is known about the changes of microbial structure during the process. In the present study, we monitored the dynamic change of microbiota in the rhizosphere of Pongamia pinnata during a 2-year on-site remediation of vanadium-titanium magnetite tailings. After remediation, overall soil health conditions were significantly improved as increased available N and P contents and enzyme activities were discovered. There was also an increase of microbial carbon and nitrogen contents. The Illumina sequencing technique revealed that the abundance of taxa under Proteobacteria was increased and rhizobia-related OTUs were preferentially enriched. A significant difference was discovered for sample groups before and after remediation. Rhizobium and Nordella were identified as the keystone taxa at genus rank. The functional prediction indicated that nitrogen fixation was enhanced, corresponding well with qPCR results which showed a significant increase of nifH gene copy numbers by the 2nd year. Our findings for the first time elucidated that legume phytoremediation can effectively cause microbial communities to shift in favour of rhizobia in heavy metal contaminated soil. Graphical abstract: Image 1 Highlights: Soil conditions were improved after phytoremediation using Pongamia pinnata. The abundance of soil Proteobacteria was increased during phytoremediation. Rhizobium and Nordella were identified to be the keystone genera during soil community shift. Soil nitrogen-fixing functions were enhanced after the legume remediation. Abstract : The main findings throw light on the changes of rhizobia community in mine tailings during its phytoremediation using Pongamia pinnat .